Ethnobotanical study of edible plants sold in Nong Muen Than Forest Product Market at Roi Et Province, Thailand - Saensouk, Surapon; Saensouk, Piyaporn; Sonthongphithak, Phiphat; Junsongduang, Auemporn; Koompoot, Kamonwan; Shen, Wei; Huang, Bin; Jitpromma, Tammanoon (Ethnobotany Research and Applications, 2026)
Background: Forest-product markets in northeastern Thailand play a crucial role in maintaining traditional food systems and transmitting local ecological knowledge. However, their ethnobotanical composition and cultural significance remain insufficiently documented. This study examines the diversity, utilization patterns, and cultural importance of edible plants sold in the Nong Muen Than Forest Product Market in Roi Et Province. Methods: Ethnobotanical data were collected through market surveys, interviews with market customers, and direct botanical identification. Quantitative analysis was conducted using the Relative Frequency of Citation (RFC) to evaluate cultural salience among recorded edible plant species. Results: A total of 88 edible plant species belonging to 42 families and 79 genera were documented. The most species-rich families were Fabaceae (10 species) and Cucurbitaceae (7 species). Over half of the species were native to Thailand (54.54%), with the remainder introduced or cultivated. Key culturally important taxa included Oryza sativa L., Curcuma singularis Gagnep., Citrus × aurantiifolia (Christm.) Swingle, Carica papaya L., and Solanum virginianum L. Wild and forest-associated vegetables, aquatic plants, and aromatic herbs were well represented, reflecting diverse landscape-based food procurement practices. RFC values ranged from 0.100 to 1.000, with seasoning plants and multipurpose vegetables receiving the highest citations from vendors. Conclusions: The Nong Muen Than Forest Product Market serves as an important repository of biocultural heritage, supporting the resilience of traditional food knowledge and the continued integration of wild, semi-wild, and cultivated edible plants into local diets. The diversity and cultural significance of these species underscore the essential role of rural markets in sustaining regional food security and culinary identity in northeastern Thailand. Keywords: edible plants; Ethnobotany; local market; Nong Muen Than Forest Product Market; Roi Et Province